The Influence Of Organizational Culture And Work Discipline On The Performance Of Employees Of The Pali Pamong Praja Police Unit (Satpol Pp) - Andriyani, Wiwin; Ermeila, Sri; Effendi, RY; Yani, Ria Astri (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
This study focuses on the analysis of the extent to which organizational culture and work discipline influence the performance of PALI Civil Service Police Unit (Satpol PP) employees. Both factors are considered to play an important role in supporting performance improvement, especially in government agencies that demand professionalism and a high level of discipline. The study was conducted quantitatively, with data obtained through surveys and interviews. The author was directly involved in data collection by distributing questionnairs to 40 respondents and conducting interviews with one of the civil servants in the PALI Satpol PP environment. Data were analyzed using multiple linear regression methods. This study revealed that organizational culture and work discipline simultannesously or together have a significant influence on the performance of PALI Satpol PP employees by 62.8%. The rest is influenced by several factors including motivation, leadership, training and development and work environment.